Sistem Pelayanan Surat Dan Pengelolaan Data Kependudukan Studi Kasus Desa Jelok Kecamatan Kaligesing Kabupaten Purworejo - Widiyanto, Dhika (Jurnal Ekonomi dan Teknik Informatika (JNETI), 2025)
Anung Wahyu Adhi "Mail Service Information System and Population System Management (Case Study: Jelok Village, Kaligesing District, Purworejo Regency)", Final Assignment for DIII Informatics Engineering Study Program under the guidance of Dhika Widiyanto, S.T, M.Kom June 2024, 82 pages + xvii + attachment. This research aims to develop an information system that supports mail services and population data management at the Jelok Village Office, Kaligesing District, Purworejo Regency. Currently, the Jelok Village Office is facing various problems in managing information and mail services, such as manual processes that cause public complaints, inaccurate information, and long queues. Apart from that, village data processing that still uses Microsoft Office creates the risk of data loss, data duplication, and data searches that take a long time. To overcome this problem, an information system was developed with features including delivering news and village activity agendas, online letter submission services, and checking the status of letter submissions. This system also includes population data management which can be accessed and processed by village officials. With this system, it is hoped that services to the community will be more effective, efficient and accurate, as well as making it easier for the community to access information and submit letters at any time without having to come directly to the village office. Keywords: information system, mail service, population data, Jelok Village Office